Particulate matter induces depression-like behavior through systemic inflammation and brain-derived neurotrophic factors - Hui Li; Xiaoyu Guo; Pengxiang Li; Xinyu Gao; Xizi Song; Xinrui Chen; Rong Liang; Jiajia Yang; Yu Li; Huaiyong Chen; Yongzhi Huang; Weiran Zhang; et al. (Environment International)
Particulate matter (PM) has always received widespread attention, PM2.5 pollution is associated with many adverse effects, including cardiovascular, respiratory and metabolic diseases and mood disorders. However, the underlying mechanisms are not yet clear. In this study, the small animal whole body inhalation exposure system collected real-time PM2.5 in the real environment, which can truly reflect the presence status of PM2.5 in the atmospheric environment. This study investigated the depressive like behavior of mice exposed to PM2.5 for a long time and proved its molecular mechanism through RNA-seq. C57BL/6 male mice were exposed to ambient air together with control mice, who breathed air filtered through high-efficiency air particulate filters. Depression like behavior was observed in mice exposed to PM for 4, 6, and 8 weeks through behavioral experiments, EEG signals, and pathological sections. RNA-seq results indicated that the depressive like behavior of mice exposed to PM2.5 might be related to pro-inflammatory and anti-inflammatory cytokines, as well as the BDNF pathways in the hippocampus and olfactory bulb. This study suggests that PM2.5 may induce depression in mice through the MAPK/CREB/BDNF pathway. Environmental Implication: Atmospheric particulate matter has been classified as Class 1 pollutant by the International Agency for Research on Cancer. Current research mainly believed that PM2.5 seriously affected lung health, but there was little research on the effects of PM2.5 on other organs. With the improvement of quality of life, people were paying more attention to mental health, while there is little research on the effects of PM2.5 on brain. This study simulated a real PM2.5 exposure environment and explored the effects of PM2.5 on the brain of mice, provided a solid scientific basis for inducing depression after PM2.5 exposure.